2023
DOI: 10.2147/idr.s419610
|View full text |Cite
|
Sign up to set email alerts
|

Drug Resistance Profile Among HIV-1 Infections Experiencing ART with Low-Level Viral Load in Guangdong China During 2011–2022: A Retrospective Study

Yun Lan,
Xuemei Ling,
Xizi Deng
et al.

Abstract: Background: Antiretroviral therapy (ART) efficiently reduces the morbidities and mortalities caused by HIV-1 infection and prevents the HIV epidemic. However, virologic failure (VF) occurs in some patients receiving ART experience, especially increases in those patients with intermittent or persistent low-level viremia (LLV). The presence of drug resistance mutations (DRMs) in LLV was a strong predictor of subsequent VF. The data on drug resistance (DR) or DRMs for HIV-1 infections at low-level viral load (LLV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…However, if the VL falls below 1000 copies/mL, the amplification success rate for drug resistance testing by genotyping will be low. In contrast, studies identified drug‐resistant mutations (DRMs) even in LLV, and the presence of DRMs in LLV strongly predicted subsequent VF [23, 24]. HIV RNA genotyping resistance testing (GRT) may not be a reliable option for PLWH with LLV due to the possibility of results being inaccurate with HIV RNA <500 copies/mL or < 1000 copies/mL [13, 25].…”
Section: Llv: Definition and Clinical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, if the VL falls below 1000 copies/mL, the amplification success rate for drug resistance testing by genotyping will be low. In contrast, studies identified drug‐resistant mutations (DRMs) even in LLV, and the presence of DRMs in LLV strongly predicted subsequent VF [23, 24]. HIV RNA genotyping resistance testing (GRT) may not be a reliable option for PLWH with LLV due to the possibility of results being inaccurate with HIV RNA <500 copies/mL or < 1000 copies/mL [13, 25].…”
Section: Llv: Definition and Clinical Implicationsmentioning
confidence: 99%
“…One study found that DRMs emerged in all ART drug classes when HIV patients had VL values of 50–999 copies/mL [27]. In a study of 2074 LLV participants, 59.21% exhibited DRMs, with 5.01%, 39.68% and 49.13% exhibiting resistance‐associated mutation patterns for PIs, nucleoside reverse‐transcriptase inhibitors (NRTIs) and NNRTIs, respectively [24]. The results of several studies suggest that to optimize ART for PLWH with LLV, GRT is necessary to explain the antiretroviral resistance profile [28, 29].…”
Section: Llv: Definition and Clinical Implicationsmentioning
confidence: 99%
“…However, HAART does not cure HIV/AIDS due to HIV latency [ [3] , [4] , [5] , [6] ] such that disruption or discontinuation of HAART leads to rebound in viremia [ [7] , [8] , [9] ]. Besides lack of cure, HAART has disadvantages with several studies reporting cases of toxicity [ [10] , [11] , [12] , [13] ], drug resistance [ [14] , [15] , [16] ] as well as other drug complications [ [17] , [18] , [19] ].…”
Section: Introductionmentioning
confidence: 99%